Impact of Si and B on the phase stability of cathodic arc evaporated Al0.70Cr0.30-based oxides. (15th July 2018) - Koller, C.M.; Dalbauer, V.; Kirnbauer, A.; Sauer, M.; Kolozsvári, S.; Ramm, J.; Mayrhofer, P.H.
Abstract: Al0.70 Cr0.30 -, Al0.665 Cr0.285 B0.05 -, and Al0.665 Cr0.285 Si0.05 -based cathodic arc evaporated oxides were investigated with respect to their structural evolution during vacuum annealing. Unalloyed (Al0.69 Cr0.31 )2 O3 crystallises with a mixed phase microstructure composed of corundum (α) and metastable cubic and γ-/θ-type phases. Alloying 5 at.% of B or Si to the cathodes results in significant grain refinement of the coatings and the suppression of the α-phase in as-deposited state. In addition, the thermally-induced phase transition from metastable into singe-phased α-structured coatings is effectively shifted from 900 °C to 950 °C or 1150 °C, respectively. Graphical abstract: Unlabelled Image